Keselamatan Universal yang diberikan Yesus Menurut Injil Lukas (Jurnal Pendidikan Agama dan Teologi, 2025)
The Gospel of Luke portrays Jesus as a universal Saviour who brings salvation to all people, regardless of race, social status, or culture. Through a narrative that emphasises love, inclusivity, and social justice, Luke shows that Jesus' mission is to save the lost, as written in Luke 19:10. Salvation in this gospel includes not only spiritual liberation from sin, but also social and physical transformation. In parables such as the Good Samaritan and the Prodigal Son, as well as His interaction with Zacchaeus, Jesus showed special concern for the poor, marginalised groups, and sinners. Jesus' inclusive approach transcends ethnic and cultural boundaries, affirming that salvation is available to all nations, as expressed in Luke 2:30-32 and Luke 1:50-55. Salvation in Luke includes life transformation that affects the heart, behaviour and social relationships. The gospel also emphasises that God's universal love drives the Church to be an inclusive community that serves all, regardless of background. Thus, Luke conveys a broad idea of salvation, which not only restores people's relationship with God, but also transforms the way we live together through love, justice and solidarity.